Preparing guiding planes for removable partial dentures: an in vitro comparison between assisted CAD-CAM template procedure and freehand preparation. (August 2022) - Bai, Hefei; Ye, Hongqiang; Chen, Hu; Wang, Yong; Zhou, Yongsheng; Sun, Yuchun
Highlights: CAD-CAM template assisted procedure can improve the clinical procedure for preparing guiding planes for removable partial dentures, respect to freehand procedures. Abstract: Objectives: To compare the trueness of computer-aided design and computer-aided manufacturing (CAD-CAM) assisted procedure and freehand procedure for preparing guiding planes for removable partial dentures (RPDs). Methods: Forty identical mandibular resin casts were divided into two groups in which the guiding planes of two abutment teeth were prepared freehand (control group, n  = 20) and using rigidly constrained templates (test group, n  = 20). The template was designed on a digital cast of virtually prepared guiding planes and fabricated by selective laser melting using cobalt-chromium alloy. To assess the 3D trueness, all prepared guiding planes (Test data) were digitized using a laboratory scanner and compared to the virtually designed guiding planes (Reference data). The angle deviation between the Test data and the designed direction of the path of placement was measured for assessing the direction trueness of guiding plane preparation. Results: The 3D trueness of guiding plane preparation was significantly better in the Test group (48.4 ± 12.9 μm) than in the Control group (128.5 ± 37.6 μm, p < 0.01). The direction trueness of guiding plane preparation was also significantly better in the Test group (1.20 ± 0.55°) than in the Control group (7.68 ± 3.00°, p < 0.01). Conclusions: The CAD-CAM template assisted procedure can significantly improve tooth preparation of the guiding planes compared to the freehand preparation. The CAD-CAM template could help clinicians prepare parallel guiding planes in a predictable manner.